An overview on antiepileptic drugs - Das N.; Dhanawat M.; Shrivastava S. (My University, 2025)
Epilepsy is the most common chronic neurological disorder of the brain. For several decades different kinds of medications have been used to treat epilepsy. Even though many surgical advances has been made and implemented, medications remain the basis of treatment. The search for noble antiepileptic drugs (AEDs) with more selective activity and lower toxicity continues to be an area of intensive investigation in medicinal chemistry. Additionally, drug resistance is an important clinical problem in epilepsy and is associated with an increased risk of morbidity and mortality. This review intends to present a comprehensive overview on AED in particular along with discussion on some aspects of associated drug resistance and combination therapy. © 2012, International Research and Cooperation Association for Bio & Socio-Sciences Advancement. All rights reserved.